Pricing insurance risk : theory and practice - Mildenhall, Stephen J.; Major, John A. (Hoboken, NJ : John Wiley and Sons, 2022)
"In order to make insurance a trade at all, the common premium must be sufficient to compensate the common losses, to pay the expense of management, and to afford such a profit as might have been drawn from an equal capital employed in any common trade. Pricing insurance risk is the last mile of underwriting. It determines which risks are accepted onto the balance sheet and makes an insurer's risk appetite operational. It is critical to successful insurance company management. As the last mile, pricing depends on all that has come before. Actuaries and underwriters have analyzed and classified the risk, trended and developed losses, and on-leveled premiums to pick a best-estimate prospective loss cost. Accountants have allocated fixed and variable expenses. Simulation models place the new risk within the context of the company's existing portfolio. The mechanics of all this work is the subject of much of the actuarial education syllabus: experience and exposure rating, predictive analytics, and advanced statistical methods. That is not the subject of this book! All of that prior effort determines the expected loss, and we take it as a given. Pricing adds the risk margin-to afford capital a reasonable return. The risk margin is our subject"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Risk (Insurance); Risk management